PERAN PEKERJA PEREMPUAN DALAM MEMENUHI EKONOMI KELUARGA: DARI PERAN DOMESTIK MENUJU SEKTOR PUBLIK - Darmin Tuwu (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2018)
This paper aims to elaborate the extent of women's role working in the informal sector at marine tourism area in Batu Gong Beach of Konawe District. This research is a qualitative research using case study approach. The data was collected using in-depth interviews, Focus Group Discussion, and observation. Interviews were conducted on 15 women who had been married and have children, who worked as rice sellers, gogos, burasa, sate pokea, beverages, cakes, candies, cigarettes, tire rentals for swimming equipment, rental mats for seat, etc. The results indicate that the role of women who work and have income play significant role to support the family finance. The income earned from selling is used to meet the needs of household life such as: as the complementary of the husband and family income; for daily shopping needs; for school’s fee and children’s expenses; and for other important needs such as when it comes to crises, severe illness, and other family problems. This study is expected to be useful for scientific development in the theme of the role of women who work in creating a prosperous family.